NETWORK ANALYSIS OF COLLABОRATIVE DECISION MAKING BY AIR NAVIGATION SYSTEM’S HUMAN-OPERATORS DURING EMERGENCY CASES IN FLIGHT - Kasatkin, Mykola; Sikirda, Yuliya; Shmelova, Tetiana (Proceedings of National Aviation University (archive), 2019)
Purpose: research of pilot and air traffic controller (ATC) collaborative decision making during emergency case in flight (for example, in case of one engine failure and other engine fires from one side during take-off on multiengine aircraft) for maximum synchronization of operators’ technological procedures. Methods: deterministic models of joint decision-making by the air navigation system operators are obtained by network planning methods; their adequacy is confirmed by full-scale modeling on a complex flight simulator. The probabilities of the emergency case development in flight are estimated using the neural network model. For the sequential optimization of the collaborative two-channel network “pilot-air traffic controller” in order to achieve the end-to-end effectiveness of joint solutions, a multi-criteria approach was used: ensuring the minimum time to parry emergency case in flight with maximum safety / maximum consistency over the time of operator actions. Results: synchronized operational procedures of air navigation system operators during emergency cases in flight with the optimal sequence of actions and the minimum time to complete the flight. A conceptual model of the system has been developed for managing and forecasting the development of emergency cases in flight based on deterministic and stochastic models of decision making by the air navigation system human operator, taking into account the influence of factors of a professional and non-professional nature. Discussion: the proposed models will complement the database of flight scenarios development in the decision support system and can be used in the air navigation system operators’ joint simulator training process and in the real conditions of aircraft exploitation.